STUDY AUTEKOLOGI PRANAJIWA (Euchresta horsfieldii (Lesch.) Benn.) DI BUKIT PENGELENGAN, DESA PANCASARI, KECAMATAN SUKASADA, KABUPATEN BULELENG, BALI - Darma, I Dewa Putu; Tirta, I Gede; Ardaka, I Made (Buletin Kebun Raya, 2011)
Pranajiwa (Euchresta horsfieldii (Lesch.) Benn) is a medicinal plant, which is growing wild and it is regarded as a rare plant. Currently, its existence in the wild increasingly threatened. Pengelengan Hill is one of the natural habitats of E. horsfieldii in Bali. Study of autecology aims to describe the ecology of E. horsfieldii in their natural habitat. E. horsfieldii was found abundant in plots II with 16.02% relative density, 9.68% of relative frequency and 25.69 of Important Value, grow clumped together with other plants (Idk 2.72).